Ultrasound-guided transversus abdominis plane block in patients undergoing laparoscopic cholecystectomy: comparison of efficacy of bupivacaine and levobupivacaine on postoperative pain control - Yıldırım Ar,Arzu (2018)
Abstract Background and objective The use of transversus abdominis plane block with different local anesthetics is considered as a part of multimodal analgesia regimen in laparoscopic cholecystectomy patients. However no studies have been published comparing bupivacaine and levobupivacaine for transversus abdominis plane block. We aimed to compare bupivacaine and levobupivacaine in ultrasound-guided transversus abdominis plane block in patients undergoing laparoscopic cholecystectomy. Methods Fifty patients (ASA I/II), undergoing laparoscopic cholecystectomy were randomly allocated into two groups. Following anesthesia induction, ultrasound-guided bilateral transversus abdominis plane block was performed with 30 mL of bupivacaine 0.25% in Group B (n = 25) and 30 mL of levobupivacaine 0.25% in Group L (n = 25) for each side. The level of pain was evaluated using 10 cm visual analog scale (VAS) at rest and during coughing 1, 5, 15, 30 min and 1, 2, 4, 6, 12 and 24 h after the operation. When visual analogue scale > 3, the patients received IV tenoxicam 20 mg. If visual analogue scale remained >3, they received IV. tramadol 1 mg.kg−1. In case of inadequate analgesia, a rescue analgesic was given. The analgesic requirement, time to first analgesic requirement was recorded. Results Visual analogue scale levels showed no difference except first and fifth minutes postoperatively where VAS was higher in Group L (p < 0.05). Analgesic requirement was similar in both groups. Time to first analgesic requirement was shorter in Group L (4.35 ± 6.92 min vs. 34.91 ± 86.26 min, p = 0.013). Conclusions Bupivacaine and levobupivacaine showed similar efficacy at TAP block in patients undergoing laparoscopic cholecystectomy.